How to raise an elephant - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series, 2020)
"The next book in the perennially adored No. 1 Ladies' Detective Agency series sees Precious Ramotswe calling upon all her maternal instincts when she's faced with a two-ton case. They say it takes a village to raise a child, but can Mma Ramotswe and the rest of the No. 1 Ladies' Detective Agency come together to raise a pipsqueak pachyderm? We may find out in this novel. We may not. Who can say?"--